Adaptation and Validation of the Tamil (Sri Lanka) Version ofthe Montreal Cognitive Assessment - Coonghe, Pethirupillai Amal Dinesh; Fonseka, Pushpa; Sivayogan, Sampasivamoorthy; Keshavaraj, Ajantha; Malhotra, Rahul; Ostbye, Truls (UI Scholars Hub, 2020)
The study aimed to develop the Tamil (Sri Lanka) version of the Montreal Cognitive Assessment (MoCA) and investigate its reliability and validity as a briefscreening tool for mild cognitive impairment (MCI). Tamil-speaking Sri Lankan elderly with normal cognition and MCI were recruited from a neurology clinic.Adaptation of the English MoCA to the Tamil (Sri Lanka) involved context-specific content modification and translation. The content validity, reliability, sensitivity,and specificity of the tool were evaluated. Study participants were 184 older adults, comprising 85 with normal cognition and 99 neurologist-diagnosed MCI.The tool had high internal consistency (Cronbach's alpha = 0.83). Receiver operating characteristic curve analyses showed an area under the curve of 0.87(95% CI = 0.83 - 0.91) for detecting MCI. The optimal cut-off score for detection of MCI was 23/24, yielded a sensitivity and specificity of 84.7% and 76.4%,respectively. The Tamil (Sri Lankan) version of the MoCA maintains its core diagnostic properties rendering it a valid and reliable tool for screening of MCIamong Tamil speaking Sri Lankan older adults.